Functional contribution of sphingosine‐1‐phosphate to airway pathology in cigarette smoke‐exposed mice. (6th November 2019) - De Cunto, Giovanna; Brancaleone, Vincenzo; Riemma, Maria Antonietta; Cerqua, Ida; Vellecco, Valentina; Spaziano, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; D'Agostino, Bruno; Lungarella, Giuseppe; Cirino, Giuseppe; Lucattelli, Monica; et al.
Abstract : Background and Purpose: A critical role for sphingosine kinase/sphingosine‐1‐phosphate (S1P) pathway in the control of airway function has been demonstrated in respiratory diseases. Here, we address S1P contribution in a mouse model of mild chronic obstructive pulmonary disease (COPD). Experimental Approach: C57BL/6J mice have been exposed to room air or cigarette smoke up to 11 months and killed at different time points. Functional and molecular studies have been performed. Key Results: Cigarette smoke caused emphysematous changes throughout the lung parenchyma coupled to a progressive collagen deposition in both peribronchiolar and peribronchial areas. The high and low airways showed an increased reactivity to cholinergic stimulation and α‐smooth muscle actin overexpression. Similarly, an increase in airway reactivity and lung resistances following S1P challenge occurred in smoking mice. A high expression of S1P, Sph‐K2, and S1P receptors (S1P2 and S1P3 ) has been detected in the lung of smoking mice. Sphingosine kinases inhibition reversed the increased cholinergic response in airways of smoking mice. Conclusions and Implications: S1P signalling up‐regulation follows the disease progression in smoking mice and is involved in the development of airway hyperresponsiveness. Our study defines a therapeutic potential for S1P inhibitors in management of airways hyperresponsiveness associated to emphysema in smokers with both asthma and COPD.